2002
DOI: 10.1074/jbc.m208755200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-induced Conformational Changes in a Mitogen-activated Protein Kinase Substrate

Abstract: Mitogen-activated protein (MAP) kinase-mediated phosphorylation of specific residues in tyrosine hydroxylase leads to an increase in enzyme activity. However, the mechanism whereby phosphorylation affects enzyme turnover is not well understood. We used a combination of fluorescence resonance energy transfer (FRET) measurements and molecular dynamics simulations to explore the conformational free energy landscape of a 10-residue MAP kinase substrate found near the N terminus of the enzyme. This region is believ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 33 publications
1
66
0
1
Order By: Relevance
“…Phosphorylation modulates protein function for example by affecting protein-protein interaction or by inducing conformational changes within the tertiary structure of the protein. One common mechanism of protein regulation is based on the phosphorylation of a site located within a flexible, solvent-exposed region of the protein (45)(46)(47). In such a case Ser/Thr phosphorylation can cause steric obstruction of the active site or induce major conformational change in the protein structure.…”
mentioning
confidence: 99%
“…Phosphorylation modulates protein function for example by affecting protein-protein interaction or by inducing conformational changes within the tertiary structure of the protein. One common mechanism of protein regulation is based on the phosphorylation of a site located within a flexible, solvent-exposed region of the protein (45)(46)(47). In such a case Ser/Thr phosphorylation can cause steric obstruction of the active site or induce major conformational change in the protein structure.…”
mentioning
confidence: 99%
“…The SR protein retains its splicing abilities even without the RS domain in vitro. Mutational studies have shown that this short motif (RS) 8 of the RS domain is phosphorylated in the cytoplasm, and the phosphorylated motif forms the nuclear localization signal (NLS) for the nuclear importation of this protein (18). The nuclear transport receptor transportin-SR2 (TRN-SR2), which is an importin-␤ family protein, binds the SR protein at the phosphorylated region of the RS domain and shuttles the SR protein into the nucleus through the nuclear pore complex (19)(20)(21).…”
mentioning
confidence: 99%
“…The answers to these questions might lie in the uniqueness of the RS dipeptide repeats and the conformation of this motif after phosphorylation. We have studied the structure of the eight RS dipeptide repeats (RS) 8 of the RS domain at atomistic detail before and after phosphorylation by using molecular dynamics simulation studies and free-energy calculations. We observed very dramatic differences between the unphosphorylated (RS) 8 and the phosphorylated form, henceforth referred to as (RpS) 8 .…”
mentioning
confidence: 99%
“…Besides increasing the negative charge of the protein, it can be hypothesized that phosphorylation-specific alterations of the quaternary structure of the GABP complex might prime it for further protein-protein interactions. One way of monitoring such structural changes of GABP in living cells is to measure the changes in energy transfer between the subunits upon phosphorylation, the so-called FRET signal (53). This involves the .…”
Section: Resultsmentioning
confidence: 99%
“…However, the consequences of GABP phosphorylation in transcriptional initiation have remained speculative, and the mechanism whereby phosphorylation would mediate transcriptional activation of GABP has remained unresolved. In fact, the mechanism whereby phosphorylation results in protein activation has been elucidated for only a few proteins (30,53), but it is likely that phosphorylation mediates protein activation through conformational allosteric changes within the tertiary and quaternary structures of the protein.…”
mentioning
confidence: 99%